Determinants of Intention to Use Mobile Phone Caller Tunes to Promote Voluntary Blood Donation: Cross-Sectional Study - Appiah, Bernard; Burdine, James N; Aftab, Ammar; Asamoah-Akuoko, Lucy; Anum, David A; Kretchy, Irene A; Samman, Elfreda W; Appiah, Patience B; Bates, Imelda (JMIR Publications, 2018)
BackgroundVoluntary blood donation rates are low in sub-Saharan Africa. Sociobehavioral factors such as a belief that donated blood would be used for performing rituals deter people from donating blood. There is a need for culturally appropriate communication interventions to encourage individuals to donate blood. Health care interventions that use mobile phones have increased in developing countries, although many of them focus on SMS text messaging (short message service, SMS). A unique feature of mobile phones that has so far not been used for aiding blood donation is caller tunes. Caller tunes replace the ringing sound heard by a caller to a mobile phone before the called party answers the call. In African countries such as Ghana, instead of the typical ringing sound, a caller may hear a message or song. Despite the popularity of such caller tunes, there is a lack of empirical studies on their potential use for promoting blood donation. ObjectiveThe aim of this study was to use the technology acceptance model to explore the influence of the factors-perceived ease of use, perceived usefulness, attitude, and free of cost-on intentions of blood or nonblood donors to download blood donation-themed caller tunes to promote blood donation, if available. MethodsA total of 478 blood donors and 477 nonblood donors were purposively sampled for an interviewer-administered questionnaire survey at blood donation sites in Accra, Ghana. Data were analyzed using descriptive statistics, exploratory factor analysis, and confirmatory factory analysis or structural equation modeling, leading to hypothesis testing to examine factors that determine intention to use caller tunes for blood donation among blood or nonblood donors who use or do not use mobile phone caller tunes. ResultsPerceived usefulness had a significant effect on intention to use caller tunes among blood donors with caller tunes (beta=.293, P<.001), blood donors without caller tunes (beta=.165, P=.02, nonblood donors with caller tunes (beta=.278, P<.001), and nonblood donors without caller tunes (beta=.164, P=.01). Attitudes had significant effect on intention to use caller tunes among blood donors without caller tunes (beta=.351, P<.001), nonblood donors with caller tunes (beta=.384, P<.001), nonblood donors without caller tunes (beta=.539, P<.001) but not among blood donors with caller tunes (beta=.056, P=.44). The effect of free-of-cost caller tunes on the intention to use for blood donation was statistically significant (beta=.169, P<.001) only in the case of nonblood donors without caller tunes, whereas this path was statistically not significant in other models. ConclusionsOur results provide empirical evidence for designing caller tunes to promote blood donation in Ghana. The study found that making caller tunes free is particularly relevant for nonblood donors with no caller tunes.